Making Human Rights a Reality - Hafner-Burton, Emilie (Book collections on Project MUSE., 2013)
In the last six decades, one of the most striking developments in international law is the emergence of a massive body of legal norms and procedures aimed at protecting human rights. In many countries, though, there is little relationship between international law and the actual protection of human rights on the ground. Making Human Rights a Reality takes a fresh look at why it's been so hard for international law to have much impact in parts of the world where human rights are most at risk. Emilie Hafner-Burton argues that more progress is possible if human rights promoters work strategically with the group of states that have dedicated resources to human rights protection. These human rights "stewards" can focus their resources on places where the tangible benefits to human rights are greatest. Success will require setting priorities as well as engaging local stakeholders such as nongovernmental organizations and national human rights institutions. To date, promoters of international human rights law have relied too heavily on setting universal goals and procedures and not enough on assessing what actually works and setting priorities. Hafner-Burton illustrates how, with a different strategy, human rights stewards can make international law more effective and also safeguard human rights for more of the world population.